The effect of current ratio and debt to equity ratio on return on equity at PT. Timah Tbk - Permada, Dewi Nari Ratih; Sari, Pitaloka (Journal of Economics and Business Letters, 2024)
This study aims to partially determine the effect of the current ratio (CR) on return on equity (ROE). To find out if there is a partial effect of Debt to equity ratio (DER) on Return On Equity (ROE). To find out if there is an effect of the Current ratio (CR) and Debt-to-equity ratio (DER) simultaneously on Return On Equity (ROE). The population in this study is the financial statements of PT. Timah Tbk for the period 2010-2021. The method used in this study is a descriptive method using an associative approach. The data used is secondary data obtained from the site www.idx.co.id. Data management is processed using the Statistical Product and Service Solution (SPSS) software program version 26.0. Data analysis used is multiple linear regression, multiple correlations, determination correlation, f-test, t-test, and testing classical assumptions, including normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests. The results of this study show that the current and debt-to-equity ratios significantly affect return on equity at pt. Timah Tbk, for the period 2010-2021, the current ratio partially does not substantially affect return on equity, while the Debt to equity ratio significantly affects return on equity. From the coefficient of determination test, it can be concluded that the two independent variables affect the return on equity at 36.5% while the system is 63.5% influenced by other factors not studied in this study.